2023
DOI: 10.1002/ueg2.12385
|View full text |Cite
|
Sign up to set email alerts
|

Food avoidance and fasting in patients with inflammatory bowel disease: Experience from the Nancy IBD nutrition clinic

Abstract: Background: Patients with inflammatory bowel disease (IBD) consider that their diet is important for controlling symptoms and frequently ask their physician for additional guidance on this matter. The objectives of the present study of patients with IBD were to characterize the prevalence of exclusion diets and fasting and to identify associated risk factors.Methods: Using an anonymous questionnaire, we screened patients attending our IBD nutrition clinic between November 2021 and April 2022 for exclusion diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Active disease and the use of small molecules or investigational drugs were associated with food avoidance. 1 This study highlights the emerging and highly prevalent phenomenon of food avoidance in patients with IBD. A recent review examining dietary behaviors in patients with IBD indicated a high prevalence of food avoidance (28%–89%), as well as restrictive dietary behavior (41%–93%).…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Active disease and the use of small molecules or investigational drugs were associated with food avoidance. 1 This study highlights the emerging and highly prevalent phenomenon of food avoidance in patients with IBD. A recent review examining dietary behaviors in patients with IBD indicated a high prevalence of food avoidance (28%–89%), as well as restrictive dietary behavior (41%–93%).…”
mentioning
confidence: 86%
“…Active disease and the use of small molecules or investigational drugs were associated with food avoidance. 1 This study…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…The prevalence of nutritional deficiencies is high among CD patients, with estimated prevalence rates of approximately 65–75% ( 12 ). The main reasons for that are related to reduced appetite, self-imposed food avoidance/restriction ( 13 ), disordered eating behavior ( 14 , 15 ), persistent mucosal and systemic inflammation, nutrient malabsorption, increased nutrient requirements, medication side effects, and high gastrointestinal losses through chronic diarrhoea, fistulas, and stomas. It is well established that poor nutritional status is a predictive factor for worse clinical outcomes in CD.…”
Section: Introductionmentioning
confidence: 99%